Advances in photoelectrochemical glucose sensors: A critical review - Oluwaseun Adepoju; Mahabubur Chowdhury; Tunde V. Ojumu (Next Nanotechnology)
Diabetes mellitus (DM) remains a major global health burden, necessitating the urgent demand for advanced diagnostic devices that enable early detection and continuous monitoring of blood glucose levels. Photoelectrochemical (PEC) sensing has emerged as a powerful alternative to conventional glucose detection strategies, offering advantages such as high sensitivity, low background signals, ease of miniaturization, and cost-effectiveness. Although interest in PEC glucose sensors (PGSs) has grown substantially in recent years, the field lacks a comprehensive and integrative review that consolidates recent advances. This article addresses this gap by presenting a critical overview of the fundamental principles of PEC sensing, commonly employed photoelectrode nanomaterials, performance enhancement strategies, and methods for fabricating photoelectrodes for glucose detection. Furthermore, it systematically examines three major categories of PGSs, comprising enzymatic, non-enzymatic, and self-powered systems, spotlighting high-ranking material designs based on critical analytical performance metrics. It also explores the growing role of density functional theory (DFT)-based computational simulations and machine learning (ML) models in predicting, optimizing, screening, and understanding sensor performance. Despite notable advancements, existing PGSs remain at the prototype stage due to persistent challenges, including suboptimal sensitivity, narrow linear detection ranges, high detection limits, low power output, poor selectivity, fabrication complexity, weak operational stability, and the lack of device-level integration. Addressing these limitations requires coordinated advances in material innovation, device architecture optimization, system integration, and scalable manufacturing to enable reliable, high-performance, and commercially viable glucose sensors.